Graphene conductive adhesive
By using raw materials such as modified epoxy resin, polyurethane, acrylic resin and graphene conductive fillers, combined with metal particles and conductive polymers, a synergistic conductive network is formed, which solves the problem of insufficient performance of existing conductive glues in high power transmission and humid and heat environments, and achieves low volume resistivity, good conductivity and durability.
Patent Information
- Application Number
- CN202411702080.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-14
AI Technical Summary
The existing conductive adhesive has a high volume resistivity in high power transmission or low resistance connections, and the contact resistance will increase in humid and heat environments, resulting in reduced circuit performance and even causing failures.
The modified epoxy resin, polyurethane, acrylic resin and graphene conductive filler are used to uniformly disperse the graphene nanosheets through stirring, ultrasonic oscillation and other processes, and combine metal particle fillers and conductive polymers to form a synergistic conductive network.
It realizes the low volume resistivity, good conductivity, durability and stability of graphene conductive glue, and is suitable for high power transmission and harsh environments, extending its service life.
Smart Images

Figure BDA0005153584640000051 
Figure BDA0005153584640000061 
Figure BDA0005153584640000062
Abstract
Description
Technical Field
[0001] The invention relates to the field of material technology, and in particular to a graphene conductive adhesive. Background Art
[0002] A transformer is a device that uses the principle of electromagnetic induction to change AC voltage. It has broad application prospects and important technical value. It mainly includes an iron core, windings, oil tanks, cooling devices, and protective devices. In the actual processing process, it is necessary to connect some parts of the transformer according to different application scenarios and needs to ensure the efficient transmission of electric energy and the realization of the electromagnetic induction process, to ensure structural stability, and to play a role in electrical isolation. For example, the connection between some parts is the only way for electric energy transmission. Appropriate connection can ensure the normal transmission of electric energy; connecting the primary winding and the secondary winding can ensure the smooth progress of the electromagnetic induction process. The working principle of the transformer involves electromagnetic induction and current transmission, and it is necessary to ensure the smooth transmission of electrical signals between some parts. Therefore, some parts need to be connected with conductive adhesives.
[0003] At present, the conductive adhesives that connect the various components in the transformer are usually composite materials composed of resin matrix, conductive particles, solvents and additives. Conductive adhesives not only provide excellent mechanical properties and bonding properties, but also have good conductivity, which can meet the needs of transformers and other electronic and electrical equipment for conductive connection.
[0004] Although conductive adhesives have various excellent properties, they still have certain defects. For example, the volume resistivity of conductive adhesives is still relatively high, which makes them unsuitable for high-power transmission or low-resistance connection. In a hot and humid environment, the contact resistance of conductive adhesive joints will increase rapidly over time, which may lead to a decrease in circuit performance or even cause failures. The conductive fillers in conductive adhesives are usually metal particles, which may migrate after long-term use or under the influence of the external environment, which will not only reduce the conductivity, but also the overall mechanical strength and stability of the conductive adhesive. Summary of the invention
[0005] The purpose of the present invention is to provide a graphene conductive adhesive, which has good conductivity, adhesion, durability, stability and dispersibility, good applicability and strong practicality.
[0006] The technical solution adopted by the present invention to solve its technical problem is:
[0007] A graphene conductive adhesive comprises the following raw materials in parts by weight: 45-55 parts of modified epoxy resin, 8-15 parts of polyurethane, 10-18 parts of acrylic resin, 18-30 parts of graphene conductive filler and 2-5 parts of N,N-dimethylaniline.
[0008] Epoxy resin is an important thermosetting resin with excellent wear resistance and low temperature flexibility, and also has the characteristics of high mechanical strength, good adhesion and good elasticity. The epoxy resin of the present invention as a matrix resin can provide the necessary bonding strength and mechanical properties for the graphene conductive adhesive. The modified epoxy resin can further improve its heat resistance, flame retardancy and storage period, so that it can better meet the preparation and application requirements of the graphene conductive adhesive of the present invention.
[0009] Polyurethane is a polymer material formed by polycondensation of polyols and polyisocyanates, and has excellent mechanical properties, plasticity, and characteristics such as oil resistance, wear resistance, low temperature resistance, and aging resistance. The present invention uses polyurethane in graphene conductive adhesive to improve the flexibility and bonding strength of the graphene conductive adhesive; and can also improve the weather resistance and chemical resistance of the graphene conductive adhesive, thereby extending its service life.
[0010] Acrylic resin has excellent weather resistance, water resistance, chemical resistance, gloss and color retention, etc. The present invention uses acrylic resin in graphene conductive adhesive to improve the film-forming performance and gloss of the conductive adhesive; and the introduction of acrylic resin can also improve the transparency and plasticity of the graphene conductive adhesive, making it easier to process and apply.
[0011] As a conductive filler, graphene can form a continuous conductive network, so that the material has a lower resistivity, thereby effectively conducting current. In the present invention, the graphene conductive filler is a key raw material for conductive performance, which provides a conductive channel to ensure that the conductive adhesive has good conductive performance. During actual processing, the graphene conductive filler is mainly added in the form of powder. The graphene conductive filler powder of the present invention is composed of graphene nanosheets, and the graphene nanosheets have a high specific surface area and excellent conductive properties. Graphene nanosheets have a high specific surface area and strength, which can enhance the mechanical properties of the conductive adhesive and improve the bonding strength and weather resistance of the adhesive. When adding the graphene conductive filler, it is usually processed by stirring, ultrasonic vibration and other processes to make the graphene nanosheets evenly dispersed in the adhesive, avoid agglomeration and sedimentation, thereby improving the stability and service life of the conductive adhesive.
[0012] N,N-dimethylaniline can be used as a catalyst or promoter in the production process of graphene conductive adhesive to accelerate the curing reaction of the resin and increase the curing speed and degree of the conductive adhesive; and the introduction of N,N-dimethylaniline can also improve the solubility and dispersibility of the graphene conductive adhesive, making it easier to mix evenly with other components.
[0013] In the present invention, the modified epoxy resin and polyurethane can provide stable structural support and excellent bonding performance, while the graphene conductive filler ensures that the conductive adhesive has good conductivity. The synergistic effect between the modified epoxy resin, polyurethane and graphene conductive filler makes the graphene conductive adhesive have both a stable structure and excellent conductivity. On this basis, the addition of acrylic resin further improves the weather resistance and chemical resistance of the conductive adhesive, so that the conductive adhesive can remain stable even in harsh environments. N, N-dimethylaniline helps dissolve and disperse the raw materials, further improving the uniformity and stability of the conductive adhesive.
[0014] Furthermore, it also includes 25-35 parts of metal particle filler, and the metal particle filler is one or more of gold, silver, copper and aluminum.
[0015] Adding metal particles to graphene conductive adhesive can significantly improve the conductive properties of the conductive adhesive, and the coordinated effect of graphene conductive filler and metal filler can further improve the conductive properties of the conductive adhesive. Specifically, the ultra-large specific surface area and high conductivity of graphene can make the metal filler more evenly dispersed between the graphene sheets, avoiding the agglomeration and sedimentation of the metal filler. At the same time, the metal particles can also fill the gaps between the graphene sheets to form a tighter conductive network, thereby improving the conductive properties of the conductive adhesive. The addition of metal particles can also improve the dispersibility of the graphene conductive filler in the matrix resin, so that the graphene conductive filler is more evenly dispersed in the resin, thereby improving the uniformity and stability of the conductive adhesive. In addition, the addition of metal particles can also improve the heat resistance of the conductive adhesive, so that it can still maintain good conductive properties under high temperature conditions.
[0016] During actual processing, the metal particle filler can be selected according to actual needs. Gold and silver are precious metals with good electrical conductivity and chemical stability. Copper and aluminum are relatively common metals with good electrical conductivity and relatively low cost. The electrical conductivity of copper is second only to silver, while aluminum has a lighter weight and good electrical conductivity, making it suitable for use in situations where weight reduction is required. Taking into account cost, conductivity and weight, the metal particle filler in the present invention adopts a composite filler of silver, copper and aluminum, and the weight ratio of the three is silver: copper: aluminum = 1:2:2.
[0017] Furthermore, it also includes 1-3 parts of a promoter and 5-15 parts of a conductive polymer.
[0018] The accelerator is one or more of 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole and 1-benzyl-2-methylimidazole. The conductive polymer is one or more of polyaniline, polypyrrole and polythiophene.
[0019] The accelerator can accelerate the curing speed of the resin in the present invention and improve the curing efficiency. The accelerator used in the present invention is mainly an imidazole accelerator, which is a class of efficient latent curing accelerators that can remain stable at room temperature, but can quickly decompose under heating or light conditions to produce substances with catalytic activity, thereby accelerating the curing reaction. Imidazole accelerators are suitable for conductive adhesives that need to be stored or transported for a long time.
[0020] After the conductive polymer is added, it can form a synergistic effect with the graphene conductive filler and the metal particles, improve the overall conductive glue and enhance its conductive properties and physical mechanical properties. In the present invention, the conductive polymer is one or more of polyaniline, polypyrrole and polythiophene, wherein polyaniline has excellent conductive properties and stability, and it is easy to combine with graphene to form a conductive network. After the present invention adds polyaniline, the conductive properties and mechanical strength of the graphene conductive glue can be improved. Polypyrrole has good conductivity and biocompatibility. When it is added to the present invention, it can form a uniform conductive layer on the surface of the graphene conductive filler by an electrochemical polymerization method, further improving the dispersibility and conductive properties of the graphene conductive glue. Polythiophene can form an effective charge transfer complex with the graphene conductive filler, thereby improving the photoelectric properties and stability of the graphene conductive glue.
[0021] The beneficial effects of the present invention are as follows: the graphene conductive glue of the present invention has low volume resistivity and good conductivity; when used as a supercapacitor electrode material, it is tested under specific charge and discharge conditions to have a large number of cycle charge and discharge times and good durability; after testing at low temperature, the thermal conductivity change rate of the present invention is low and has good stability; it exhibits good bonding properties at different temperatures; and the graphene conductive glue of the present invention has good dispersibility and strong practicality. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the following will be described clearly and completely in combination with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are partial embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention.
[0023] Example 1
[0024] A graphene conductive adhesive comprises the following raw materials in parts by weight: 45 parts of modified epoxy resin, 8 parts of polyurethane, 10 parts of acrylic resin, 18 parts of graphene conductive filler, 2 parts of N,N-dimethylaniline, 25 parts of metal particle filler, 1 part of accelerator and 5 parts of conductive polymer.
[0025] The modified epoxy resin, polyurethane and acrylic resin in this embodiment are all common raw materials on the market. In this embodiment, the modified epoxy resin is S-931 water-based acrylate modified epoxy resin; the polyurethane adopts commercially available polyester polyurethane; the acrylic resin adopts pure acrylic resin with model number SA3710, which has good adhesion, weather resistance and chemical stability. The conductive adhesive prepared by combining it as a raw material with other raw materials of the present invention has good adhesion and durability.
[0026] In this embodiment, the metal particle filler is a metal nanoparticle composite filler of silver, copper and aluminum, and the weight ratio of the three is silver: copper: aluminum = 1:2:2.
[0027] In this embodiment, the accelerator is compounded with 2-methylimidazole and 2-ethyl-4-methylimidazole, and the weight ratio of the two is 2-methylimidazole:2-ethyl-4-methylimidazole=2:1.
[0028] In this embodiment, the conductive polymer is a composite of polyaniline, polypyrrole and polythiophene, and the weight ratio of the three is polyaniline: polypyrrole: polythiophene = 1:1:1.
[0029] The preparation method of the graphene conductive adhesive of the present invention mainly comprises the following steps:
[0030] Step S1, mixing the raw materials, mixing the modified epoxy resin, polyurethane and acrylic resin in the above proportions, adding graphene conductive filler, metal particle filler and conductive polymer after stirring evenly, continuing to stir so that the filler is evenly dispersed in the resin to obtain a mixture A, and slowly adding N,N-dimethylaniline during the stirring process to improve the fluidity and processing performance of the mixture.
[0031] Step S2, dispersion and stirring, using mechanical stirring, ultrasonic dispersion and other methods to process the mixed material A in step S1 to obtain mixed material B. This method is used to evenly disperse the graphene conductive filler and the metal particle filler in the resin matrix to ensure good contact and bonding between the fillers and between the fillers and the resin matrix.
[0032] Step S3, adding an accelerator, adding the accelerator to the mixed material B in step S2, and then stirring until the accelerator is evenly distributed in the mixed material B, to obtain a mixed material C.
[0033] Step S4, curing treatment, pouring the mixture C into the mold and curing it, the curing temperature is 120℃~140℃, and the curing time is 1.5h~2h. The preferred curing temperature of the present invention is 120℃, and the curing time is 1.8h to ensure that the conductive adhesive is completely cured and forms a good conductive network.
[0034] Embodiment 2-5
[0035] The raw materials and processing methods of Examples 2-5 are exactly the same as those of Example 1, and the only difference is the amount of the raw materials used. A comparison table of the raw material amounts of Examples 2-5 and Example 1 is shown in Table 1 below.
[0036] Table 1 Comparison of raw material usage of Examples 2-5 and Example 1
[0037]
[0038] The performance of the graphene conductive adhesive prepared in Examples 1-5 was tested. The graphene conductive adhesive products prepared in Examples 1-5 of the present invention were respectively used as experimental groups, named experimental groups 1-5, and commercially available common conductive adhesives were randomly selected as controls, named control groups. Various samples were taken for conductivity, adhesion, durability, stability and dispersibility tests, wherein the specific test results of conductivity, durability, stability and dispersibility are shown in Table 2 below; the specific test results of adhesion are shown in Table 3 below.
[0039] Table 2 Specific test results of conductivity, durability, stability and dispersibility of experimental groups 1-5 and comparison group
[0040]
[0041] Table 3 Specific test results of adhesion of experimental groups 1-5 and comparison group
[0042]
[0043]
[0044] According to the results in Table 2 and Table 3, the graphene conductive adhesive of the present invention has better conductivity, durability and stability than the commercially available conductive adhesive, and the volume resistivity can be as low as 3.17×10 -5 Ω·cm; the maximum number of charge and discharge cycles can reach 1241 times; at low temperature (-20°C), after 1000 hours of aging test, the thermal conductivity change rate is as low as ±8%. And it has good adhesion at different temperatures. Even in low temperature environment, the minimum bonding strength is 20.1MPa. In experimental groups 1-5, the various performances of experimental group 4 are significantly better than those of other experimental groups. Therefore, in embodiments 1-5, embodiment 4 is preferred as the best embodiment. Although embodiments 1-5 have good conductivity, adhesion, durability and stability, the overall dispersibility is not ideal, so the present invention also designs embodiments 6-8.
[0045] Embodiment 6-8
[0046] Embodiments 6-8 are improvements made on the basis of Embodiment 4, and Embodiments 6-8 have the following differences compared with Embodiment 4:
[0047] The raw materials of Examples 6-8 also include 1-3 parts of sodium lauryl sulfate and 2-5 parts of polyethylene glycol;
[0048] In the preparation process of Examples 6-8, sodium lauryl sulfate and polyethylene glycol were added at the same time as the accelerator was added in step S3.
[0049] Sodium dodecyl sulfate and polyethylene glycol as surfactants can adjust the interaction between graphene and the carrier by introducing hydrophobic or hydrophilic groups, thereby achieving efficient graphene dispersion. Specifically, sodium dodecyl sulfate can stabilize the graphene dispersion system through electrostatic repulsion and steric hindrance effects, and polyethylene glycol can bind to graphene through interactions such as hydrogen bonds and van der Waals forces, thereby achieving effective dispersion of graphene.
[0050] The comparison table of raw material dosage of Examples 6-8 and Example 4 is shown in Table 4 below.
[0051] Table 4 Comparison of raw material usage of Examples 6-8 and Example 4
[0052]
[0053] The conductivity, adhesion, durability, stability and dispersibility of Examples 6-8 (each group is named experimental group 6-8) were tested using the methods of Examples 1-5. The specific test results of conductivity, durability, stability and dispersibility are shown in Table 5 below; the specific test results of adhesion are shown in Table 6 below.
[0054] Table 5 Specific test results of conductivity, durability, stability and dispersibility of experimental groups 6-8 and experimental group 4
[0055]
[0056] Table 6 Specific test results of adhesion of experimental groups 6-8 and experimental group 4
[0057]
[0058]
[0059] According to the results of Table 5 and Table 6, the present invention significantly improves the conductivity after adding sodium dodecyl sulfate and polyethylene glycol, and has little effect on durability, stability and adhesion, but significantly improves the dispersibility of the system, and the graphene sheets are evenly dispersed without obvious agglomeration, and the dispersibility is good. In experimental groups 6-8, the overall test improvement effect of experimental group 7 is more obvious, therefore, in embodiments 6-8, embodiment 7 is preferred as the best embodiment.
[0060] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the scope of the present invention should be included in the protection scope of the present invention.
Claims
1. A graphene conductive adhesive, characterized in that: The invention comprises the following raw materials in parts by weight: 45-55 parts of modified epoxy resin, 8-15 parts of polyurethane, 10-18 parts of acrylic resin, 18-30 parts of graphene conductive filler and 2-5 parts of N,N-dimethylaniline.
2. The graphene conductive adhesive according to claim 1, characterized in that: The invention also comprises 25-35 parts of metal particle filler, and the metal particle filler is one or more of gold, silver, copper and aluminum.
3. The graphene conductive adhesive according to claim 1 or 2, characterized in that: It also includes 1-3 parts of a promoter and 5-15 parts of a conductive polymer.
4. The graphene conductive adhesive according to claim 3, characterized in that: The accelerator is one or more of 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole and 1-benzyl-2-methylimidazole.
5. The graphene conductive adhesive according to claim 3, characterized in that: The conductive polymer is one or more of polyaniline, polypyrrole and polythiophene.
6. The graphene conductive adhesive according to claim 4, characterized in that: The conductive polymer is one or more of polyaniline, polypyrrole and polythiophene.
Citation Information
Cited By
Light-storage integrated cement-based curtain wall plate based on cement-based super capacitor
CN120925597A